Effect of Intravitreal Aflibercept on Wet Age-Related Macular Degeneration and Evaluation of Risk Factors on Patient’s Response: Doi: 10.36351/pjo.v39i3.1583 - Alkazraji, Rasha Abdulelah Mustafa; Ali , Samara M; Hussein , Zaid Rajab (Pakistan Journal of Ophthalmology, 2023)
Purpose: To evaluate the effect of intravitreal Aflibercept injection on wet AMD both functionally and anatomically after loading doses. The secondary aim is to evaluate the effect of risk factors including (gender, age, smoking, hypertension, and diabetes meatus) on the patient’s response. Study Design: Interventional case series. Place and Duration of Study: Al-Haitham Eyes Teaching Hospital in Baghdad, Iraq, from November 2021 and September 2022. Methods: Fifty eyes of 47 patients with treatment naïve wet AMD were selected through convenient sampling. Data were collected for age, gender, smoking, and chronic disease. Clinical examination, best corrected visual acuity (BCVA), optical coherence tomography angiography, and spectral domain optical coherence tomography SD-OCT were performed at baseline and then at 16 weeks, after three one-monthly injections of Aflibercept 2 mg/ 0.05 ml intravitreally. Results: Mean age was 68.23 ± 8.5 years. Mean difference in BCVA was 0.37 ± 0.03 (P = 0.000) and mean difference in central macular thickness was 105.72 ± 45.05 (P value < .0000) at 16 weeks. CNV was associated with intra-retinal fluid in 52% of cases, subretinal fluid in 72%, pigment epithelial detachment in 20%, intraretinal hemorrhage in 6% and subretinal hemorrhage in 4%. Studying associations between the responses of Aflibercept with the general features of the patients as age, gender, chronic diseases and smoking status, revealed no statistically significant difference. Conclusion: This study demonstrates that aflibercept is effective for the treatment of patients with wet AMD both functionally and anatomically after the loading doses. The presence of intraretinal fluid at presentation had a negative effect on the vision.